Factors Influencing MICE Tourism Development In Pulau Seribu, Jakarta, Indonesia - Ghaffara, Jihad; Currie, Gareth; Rahmitasari, Nurima (Jurnal Penelitian Pariwisata, 2018)
This research aims to investigate the factors influencing MICE development in Pulau Seribu. Primary research data are collected by using questionnaire to analyse the market condition, demand, and potential factors in MICE industry. The results discover that the main factors influencing MICE tourism development in Pulau Seribu are infrastructure and marketing. In addition, the research has found that service provider industry is the main target market as meeting and incentives trip for the potential target market as an MICE tourism activity. Also, this research shows the correlation with the theory of infrastructure as one of the most factors that can influence MICE tourism by Swarbrooke & Horner (2001), and Nawrocka theory (2013).